Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Suppose that $f$ is continuous at $x_0$ and $f$ satisfies $f(x)+f(y)=f(x+y)$. Then how can we prove that $f$ is continuous at $x$ for all $x$? I seems to have problem doing anything with it. Thanks in advance.

share|cite|improve this question
$f(x)-f(b)=f(x-b+a)-f(a)$. – André Nicolas Dec 24 '11 at 4:26
@Sabyasachi: I have edited your question. Check if this is what you would like to ask. – Paul Dec 24 '11 at 4:28
Thank you.That's what I meant. – Eisen Dec 24 '11 at 4:40
In fact, you can do more. A solution $f$ to the Cauchy equation $f(x+y)=f(x)+f(y)$ is not of the form $f(x)=mx$ if and only if its graph $$\Gamma=\{(x,f(x)):x\in\mathbb{R}\}$$ is dense in $\mathbb{R}^{2}$. – Sangchul Lee Dec 24 '11 at 15:16
up vote 15 down vote accepted

Fix $a\in \mathbb{R}.$


$\begin{align*}\displaystyle\lim_{x \rightarrow a} f(x) &= \displaystyle\lim_{x \rightarrow x_0} f(x - x_0 + a)\\ &= \displaystyle\lim_{x \rightarrow x_0} [f(x) - f(x_0) + f(a)]\\& = (\displaystyle\lim_{x \rightarrow x_0} f(x)) - f(x_0) + f(a)\\ & = f(x_0) -f(x_0) + f(a)\\ & = f(a). \end{align*}$

It follows $f$ is continuous at $a.$

share|cite|improve this answer
Doesn't this work in any topological group? – dfeuer Dec 25 '11 at 16:18

Let's examine your situation. You have that $\lim_{x\rightarrow a} f(x) = f(a)$ for some $a\in \mathbb{R}$ and that for any $x,y\in \mathbb{R}, f(x)+f(y)=f(x+y)$. You want to prove that for any $c\in \mathbb{R}, \lim_{x\rightarrow c} f(x) = f(c)$. The key step here is to realize that $$\lim_{x\rightarrow c} f(x) = \lim_{x\rightarrow a} f(x-a+c)$$ because $|(x-a+c)-c| = |x-a|$, so in plain english $x$ is close to $a$ if and only if $x-a+c$ is close to $c$. We can then complete the proof as follows: $$\lim_{x\rightarrow a} f(x-a+c) = \lim_{x\rightarrow a} (f(x) + f(c-a)) = f(a) + f(c-a) = f(c)$$

share|cite|improve this answer

Suppose $x=x_0, f(x_0) + f(y) = f(x_0 + y)$ taking limit as $y$ tends to $0$, we get $\lim_{y\rightarrow 0} (f(x_0) + f(y)) = \lim_{y\rightarrow 0} f(x_0 + y)$ From the continuity at $x_0$, we know that RHS of the above equation is $f(x_0)$ which means that $\lim_{y\rightarrow 0} f(y) =0$

Next bit it simple. For any $x,y$ in the domain, $f(x+y)=f(x)+f(y)$ continuity can be established by checking whether $\lim_{y\rightarrow 0} f(x+y) =f(x)$ which is true since $f(x+y)=f(x)+f(y)$ and $\lim_{y\rightarrow 0}f(y)=0$. Hence $f(x)$ is continuous everywhere in the domain.

I'm new here so I don't know how to input equations using latex. Pls bear with it.

share|cite|improve this answer
To format equations in LaTeX, you simply place dollar signs around the expression. For example, \$f(y)\$ gives $f(y)$. Of course, there a more things you can do beyond this to get nicer format. I will edit your answer to put everything into LaTeX, and you can right-click on the expressions and select "view source" to see how to format them in LaTeX. – Alex Becker Dec 24 '11 at 4:41

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.